Development of Regulations on Factual Actions Post-Law on Government Administration: 2024 Election Process Dispute Study in Casu Prima Political Party - Said, Ahmad; Herawati, Ratna; -, Sulistiani (Program Studi Hukum Keluarga Islam, 2024)
Factual actions in state administrative law have experienced developments after the issue of government administration law. This factual action is active in nature and is always preceded by a written decision from state administrative officials (TUN). However, in practice, factual actions involving written decisions are still subject to district courts accepting claims for unlawful acts (PMH) such as official decisions of state administrative officials (TUN) which are naturally the public law. This can be seen in the Jakarta District Court Decision Number: 757/Pdt.G/2022/PN which has punished the General Election Commission of the Republic of Indonesia (KPU RI) to postpone the General Election (Pemilu) and pay compensation. The aim of the research is to analyze the problems of the authority of written factual actions and to reformulate fair laws in the PTUN judicial system as well as the amount of awarded compensation procedures. Meanwhile, this research uses normative legal methods with statutory, conceptual and case approaches. The data collection method is by means of secondary data. The results of this research show that in the development of factual actions in state administrative law there has been an expansion of meaning to include written decisions, so that if there is a dispute over the election process between participants and the organizers of the General Election (Pemilu) then dispute resolution becomes the realm of absolute competence of the State Administrative Court (PTUN) after taking legal adjudication efforts at the Election Supervisory Body (Bawaslu). For this reason, in the future, legal reformulation efforts are needed regarding the expansion of the meaning of written decisions to also include factual actions contained in Law Number 51 of 2009 concerning PTUN, and changes to Government Regulation Number 43 of 1991 in the nominal amount of compensation awarded in PTUN according to real conditions regarding factual actions that give rise to PMH by the government.